Genetic analysis of patients with chronic active hepatitis. - Page, A R (1975)
21 patients with chronic active hapatitis (CAH) and their families were HL-A typed. HL-A8 was significantly increased in frequency. An apparent increased frequency of HL-A1 was shown to be secondary to the increased HL-A8 due to linkage disequilibrium. Genotype analysis revealed a striking increased frequency of homozygosity for HL-A8, 6 of 21 patients (28.5%) vs. 2.8% of controls. Two patients and one normal who were homozygous for both HL-A1 and HL-A8 were found to be homozygous for a mixed lymphocyte culture (MLC) determinant 8a. Homozygous 8a cells were used as test-stimulating cells in one-way MLC reactions to determine the frequency of the expression of the 8a determinant in 17 patients and 49 controls selected for HL-A type. 8a was found to be associated with 50% of HL-A8 haplotypes and was frequent in the patient and control populations of the same HL-A types. These data suggest that susceptibility to CAH is determined by homozygosity for a gene that is in linkage disequilibrium with HL-A8 and more closely associated with the HL-A second locus then with the locus for the major MLC determinant.